Pemberatasan Tindak Pidana Terorisme di Indonesia (Analisis Terhadap Undang-Undang Nomor 15 dan 16 Tahun 2003 Berdasarkan Teori Hukum) - Ahmad Mukri Aji (Jurnal Cita Hukum, 2013)
Eradicating Criminal Acts of Terrorism in Indonesia: Legal Theory Perspective. The terrorist attacks on September 11th 2001 has fundamentally changed the United States and the world's understanding towards the dangers posed by terrorism. As a result, the Act (Act) Anti-Terrorism Law No. 15 and 16 of 2003 was regulated and legalized by the House of Representatives (DPR). Anti-Terrorism Act is expected to provide support functions as a component of the rule of law and a fair legal basis, and effectively prevent the occurrence of acts of terrorism. This article focused on analyzing the anti-terrorism act based on the applicable legal theory. DOI: 10.15408/jch.v1i1.2980